The awareness of health professionals about the importance of early diagnosis of Retinoblastoma: literature review (Research, Society and Development, 2023)
Objective: This article aims to analyze the publications that deal with the knowledge of primary health care professionals about the importance and need for early diagnosis for possible success in the treatment of retinoblastoma. Methodology: a search was performed on the BVS, SciElo and PubMed platforms, using the descriptors: early diagnosis, retinoblastoma, health professional and primary health care, and 11 articles were found. As an inclusion criterion, scientific articles published in indexed journals were used, addressing the proposed theme, which could be field studies or reviews in Portuguese and English, between August 2017 and August 2022, excluding articles that did not talk about the diagnosis of retinoblastoma, were not in the format of duplicate scientific articles, those whose results were not related to the proposed topic or that were not available in full or free of charge, leaving 03 articles for analysis. The Boolean operators used to select articles were AND and OR. Results and discussions: classified as lateral, bilateral or trilateral. Arising from autosomal dominant genetic mutations, prevalent in 1 case in every 15,000 to 18,000 live births. Leukocoria is the predominant sign, and can be detected by exams: ultrasonography, computed tomography, magnetic resonance and fluorescein angiography. The most used treatment is based on an American classification that divides cases into categories (a, b, c and d). Categories a and b are treated with local procedures and categories c and d with chemotherapy. Conclusion: the success of the treatment depends on early diagnosis and support from family members for the child's adherence to treatment.